4th Aircraft Structural Design Conference : conference programme & proceedings, 7-9, October 2014 Queen's University Belfast. (Royal Aeronautical Society, 2014)
The Royal Aeronautical Society's 4th Aircraft Structural Design Conference undertaken with the support of Queen's University Belfast will address the challenges facing the designers of the next generation aircraft. These challenges arise because the new designs will need to meet strict environmental constraints, be subject to ever increasing pressures to reduce manufacturing and life-cycle costs and for continual improvements in overall performance/efficiency factors. The resulting aircraft will be complex, requiring multi-disciplinary design approaches and solutions in a distributed design environment. The 4th Aircraft Structural Design Conference is hosted by Queens University Belfast which is internationally recognised as a leading university devoted to teaching and research in engineering with particular expertise in aeronautical engineering.
Keywords: Airframes -- Design and construction.; elektronické knihy; electronic books